38.3: Fast Ferroelectric Liquid Crystal Modes Based on Photoaligning Technology. Issue 1 (1st July 2013) - Chigrinov, Vladimir; Pozhidaev, Eugene; Srivastava, Abhishek; Qi, Guo; Ying, Ma; Kwok, Hoi Sing
Abstract: Fast response time, high contrast ratio various FLC electrooptical modes are achieved through the application of photoaligning layers in FLC cells. Fast FLCD with a high resolution can be used in the screens field sequential color (FSC) FLC microdisplays, which are now one of the most advanced technologies for pico‐projectors.